Pentingnya Melatih Komunikasi dengan Metode Bermain pada Anak Usia Dini - Dinda Aprilia; Amelia Triashari; Ulfa Dwi Anti; Ade Agustina; Aman Simaremare; Elya Siska Anggraini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
It is so important to train communication in early childhood. Often children are silent and lazy to do an activity will result in communication skills in children not growing well. In fact, communication skills play an important role in a child's life. Children's good communication skills come from activities that children usually do in their world, namely through playing. However, it is very regrettable if the world for children's play is very sporadic, even difficult to produce. The limited playground for children causes children to be more interested or choose to play inside the house by playing gadgets, watching television although this has several positive impacts, but it makes children no longer interested in playing outside such as playing chase, cats, sobyong and others so that children do not socialize with their peers which can hinder the development of early childhood communication. Therefore, the development of early childhood communication is very important to be developed from an early age. Playing can train children's communication, not only that, but also some aspects of development children.